Avaliação do impacto produtivo, econômico e ambiental de um sistema de alimentação de precisão para suínos - Andretta, Ines (2014)
The impact of switching from a conventional to a precision feeding system on pig performance, nutrient balance and feed costs in growing-finishing pigs was evaluated over 84 days in two studies. In the first trial, 60 pigs (41.2 ± 3.9 kg) were used to compare a commercial three-phase feeding program; a control three-phase feeding program, in which pigs were fed within each phase with a constant blend of feeds containing high or low nutrient density; and two multi-phases feeding programs, in which the same feeds were blended daily to meet the nutritional requirements either of the group or of each pig individually. In the second trial, 70 pigs (30.4 ± 2.2 kg) were fed according to five feeding programs: a three-phase control program equivalent to the one used in trial 1 and four multi-phase feeding programs, in which pigs were fed daily with a blend meeting 110%, 100%, 90% or 80% of the estimated individual nutritional requirements. Feed intake was recorded automatically in the feeders and pigs were weighted weekly during the trials. Nitrogen and phosphorus excretions were calculated as the ratio between retention (estimated through densitometer scanning each 28 days) and intake. Feeding pigs with diets tailored daily to individual lysine requirements allowed obtaining similar (P > 0.05) feed intake and weight gain results in comparison with the control treatment in both trials. However, precision feeding reduced (P < 0.05) the digestible lysine intake by 27% and 26%, the estimated nitrogen excretion by 22% and 30%, and feeding costs by 8% and 10% in the first and second studies, respectively, in comparison with the control three-phase treatment. Precision feeding is an effective approach to reduce nutrient excretion and feed costs without interfering on pig performance.